2008
DOI: 10.1007/s10530-008-9314-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of priority effects and pond location on invaded larval amphibian communities

Abstract: In Florida, the Cuban Treefrog (Osteopilus septentrionalis) is a superb colonist and appears to be a significant driver of amphibian community dynamics. Decline of native anurans has been linked to possible competition with adult O. septentrionalis but interactions during the larval stage are largely unknown. Rearing O. septentrionalis tadpoles along with two native anurans, the Squirrel Treefrog (Hyla squirella) and the Southern Toad (Bufo terrestris) in both experimental artificial ponds and laboratory aquar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…These findings contrasted our results, which indicated that Bufo did best (survival, larval period) when introduced early. However, results similar to ours have been reported by Crossland et al (2009) for cane toads (B. marinus, 100/m 3 ), and by Knight et al (2009) for southern toads (B. terrestris, 10-20/m 3 ). The Bufo mass response in our study may have been affected by the substantially greater survival of tadpoles that were introduced early, which could have depressed mass at metamorphosis through greater intraspecific competition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings contrasted our results, which indicated that Bufo did best (survival, larval period) when introduced early. However, results similar to ours have been reported by Crossland et al (2009) for cane toads (B. marinus, 100/m 3 ), and by Knight et al (2009) for southern toads (B. terrestris, 10-20/m 3 ). The Bufo mass response in our study may have been affected by the substantially greater survival of tadpoles that were introduced early, which could have depressed mass at metamorphosis through greater intraspecific competition.…”
Section: Discussionsupporting
confidence: 92%
“…Boone et al (2002) found that time of hatching of marbled salamanders influenced whether or not they were competitors or predators of mole salamanders; whether or not marbled salamander larvae gained a growth advantage over mole salamander larvae varied among years depending on time of pond filling and egg nest position within the habitat. Knight et al (2009) showed that colonization history and pond location (full sun or shaded) governed whether invasive exotic treefrog tadpoles could preclude native tadpoles from reaching metamorphosis. Heterospecifics may also be competitors or intra-guild predators, depending either on when they colonize the system Margalit 1994, 1996;Sours and Petranka 2007) or on which species are present (Wilbur 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Alford 1999), several studies have evaluated the possible impact of competition from non-native tadpoles on native tadpoles (Kupferberg 1997;Crossland 1998;Kiesecker and Blaustein 1998;Smith 2005;Knight et al 2009;Crossland and Shine 2010;Rebelo et al 2010) and their effects on community structure; although only a few of these studies were carried out on arid or Mediterranean amphibian communities (Woodward 1982;RichterBoix et al 2007a;Escoriza and Boix 2012). The competitiveness of the different species can be quantified using tadpole performance measures such as larval period, size at metamorphosis and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Wilbur 1977;Katzmann et al 2003;Richter-Boix et al 2007), mediated not only by direct reduction in per-capita food availability (Steinwascher 1979;Dash and Hota 1980), but also via more subtle means such as response to chemical substances produced by developing larvae (Rose 1960;Licht 1967;Beebee 1991). A range of life-history shifts has been documented in response to such competitive forces, with the responses that we saw in Marbled Frogs (no change in tadpole survival, but production of small, late-emerging metamorphs) being a common outcome of larval competition between introduced and endemic larval anurans (Kupferberg 1997;Williamson 1999;Smith 2005;Knight et al 2009). …”
Section: Discussionmentioning
confidence: 85%
“…To avoid pseudoreplication, we used means of each container for duration of larval period and mass at metamorphosis in our statistical analyses. We used multivariate analysis of variance (MANOVA) to test for differences between groups raised with, versus without toad tadpoles present (see Morin 1983;Alford 1989;Knight et al 2009). Three dependent variables were used: proportion surviving to metamorphosis, duration of larval period and mass at metamorphosis.…”
Section: Measurements and Statistical Analysismentioning
confidence: 99%